Effects of different mulching materials on yield and yield components of maize (Zea mays L.) - Zin Mar Aung; Thu Zar (Future Science, 2023)
Two field experiments were conducted during dry season (October, 2019 to March, 2020) at Yezin Agricultural University farm and Sepin research farm, Yamethin, Myanmar to investigate the effect of different mulching materials on yield and yield components of maize. No mulching and six mulching materials (rice straw mulching, rice husk mulching, maize stover mulching, mung bean stover mulching, soybean stover mulching and white plastic polyethylene mulching) were laid in a Randomized Complete Block Design (RCB) with three replications on NK-621 variety. The longest days to 50% tasseling (69.67) at Yezin and (71.67) at Yamethin were obtained in no mulching while the shortest days to 50% tasseling (62.00) at Yezin and (64.33) at Yamethin were observed from rice straw mulching at Yezin and white plastic polyethylene mulching at Yamethin. Number of kernel row-1, rows ear-1, row length, kernels ear-1, thousand grains weight were significantly different among different mulching materials at Yezin. The maximum grain yield (5.72 ton ha-1) and (10.39 ton ha-1) were observed from rice straw mulching at Yezin and Yamethin. According to the results, rice straw mulching resulted in the highest yield and yield components of maize at two locations.